Implementasi Penyelesaian Perselisihan Hak atas Pembayaran Upah Lembur pada PT. HI Kota Jambi Berdasarkan Undang-Undang Nomor 2 Tahun 2004 tentang Penyelesaian Perselisihan Hubungan Industrial - Muhammad Sakri; Taryanto (Jurnal Hukum Lex Generalis, 2026)
This study aims to analyze the legal regulation and implementation of Industrial Relations Dispute Settlement under Act Number 2 of 2004 regarding disputes over overtime wage payments at PT. HI Jambi City. This research employed an empirical juridical method through library research and interviews. The findings indicate that dispute resolution has been carried out through bipartite negotiations in accordance with the Act, although obstacles remain, including delayed overtime payments, inadequate overtime recording and limited workers' understanding of their statutory rights. Therefore, optimizing the dispute settlement mechanism is necessary to ensure legal certainty, justice and legal benefit.